Mapping ligand binding pockets in chloride ClC‐1 channels through an integrated in silico and experimental approach using anthracene‐9‐carboxylic acid and niflumic acid. (6th April 2018) - Altamura, C; Mangiatordi, G F; Nicolotti, O; Sahbani, D; Farinato, A; Leonetti, F; Carratù, M R; Conte, D; Desaphy, J‐F; Imbrici, P
Abstract : Background and Purpose: Although chloride channels are involved in several physiological processes and acquired diseases, the availability of compounds selectively targeting CLC proteins is limited. ClC‐1 channels are responsible for sarcolemma repolarization after an action potential in skeletal muscle and have been associated with myotonia congenita and myotonic dystrophy as well as with other muscular physiopathological conditions. To date only a few ClC‐1 blockers have been discovered, such as anthracene‐9‐carboxylic acid (9‐AC) and niflumic acid (NFA), whereas no activator exists. The absence of a ClC‐1 structure and the limited information regarding the binding pockets in CLC channels hamper the identification of improved modulators. Experimental Approach: Here we provide an in‐depth characterization of drug binding pockets in ClC‐1 through an integrated in silico and experimental approach. We first searched putative cavities in a homology model of ClC‐1 built upon an eukaryotic CLC crystal structure, and then validated in silico data by measuring the blocking ability of 9‐AC and NFA on mutant ClC‐1 channels expressed in HEK 293 cells. Key Results: We identified four putative binding cavities in ClC‐1. 9‐AC appears to interact with residues K231, R421 and F484 within the channel pore. We also identified one preferential binding cavity for NFA and propose R421 and F484 as critical residues. Conclusions and Implications: This study represents the first effort to delineate the binding sites of ClC‐1. This information is fundamental to discover compounds useful in the treatment of ClC‐1‐associated dysfunctions and might represent a starting point for specifically targeting other CLC proteins.